PENGARUH METODE PEMBELAJARAN PICTORIAL RIDDLE TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA SD PADA MATERI PELESTARIAN LINGKUNGAN - Surtriyanti, Euis; Panjaitan, Regina Lichteria; Sudin, Ali (Jurnal Pena Ilmiah, 2017)
Critical thinking will appear in students during the learning exercises, the teacher is able to build patterns of interaction and student communication actively. One of the best learning methods used to improve students' thinking skills is the Pictorial Riddle method. The sample of this research is the fourth grade students of SDN Ranjiwetan I, SDN Ranjiwetan IV, and SDN Ranjiwetan V which are all three as experimental class. The instruments used in this study are test and non test. As the results of research with significance level = 0.05 indicates the method of learning. Riddle can improve high, medium, and low thinking skills. However, there is no average difference between mindset in high, medium, and low group. Students' responses in learning using the Pictorial Riddle method by teachers are very high.